Removal of Eriochrome Black T (EBT) and Its Pb(II)-, Cu(II)-, and Zn(II)-Based Metal Complexes from Aqueous Solutions Using Spent Coffee Grounds: Part A – Characterization and Adsorption Isotherms - Ashraf Al-Msiedeen; Rasheed M. A. Q. Jamhour; Rand Al-Faraheed; Muayad Esaifan; Mohannad Jamhour; Mustafa J.A. Abualreish (Journal of Applied Science and Engineering, 2025)
The spent coffee grounds (SCG) waste was converted into an adsorbent through minimal washing. The efficiency of this low-cost adsorbent was evaluated based on its ability to remove the azo dye Eriochrome Black T (EBT) and its metal ion complexes from wastewater, which are commonly present in industrial effluents. Temperature, pH, contact time, adsorbent dose and initial dye concentration were among the variables that have been assessed by fixed bed column adsorption and a batch method. Brunauer-Emmett-Teller (BET) method BET, Fourier-transformed infrared (FTIR) spectroscopy, and scanning electron microscopy (SEM) were utilized for characterization. Elimination of EBT and their compounds was consistent with Freundlich isotherm form. At an equilibrium period, the adsorption ability of EBT was 4.95 mg/g; and that of the complexes [EBT-Pb(II)], [EBT-Cu(II)], and [EBT-Zn(II)] was 4.72, 4.70, and 4.53 mg/g, respectively.